Keakuratan Materi Buku Teks Pendamping Bahasa IndonesiaSMP Kelas VIII Kurikulum 2013 - Hayati, Noer, Laili Etika Rahmawati, S. Pd, M. Pd (2016)
Problem based of the study is material accuration indonesian language text book eight grade (8 th ) junior high school curriculum 2013. The aim of this study to describe about material accuration indonesian text book eight grade (8 th ) junior high school curriculum 2013. This study belong to qualitative research. The method used in this study is qualitative descriptive. Data of this study is discourse and sentence in indonesian language text book eight grade (8 th ) junior high school curriculum 2013. Collecting technique of data is documenter study and book investigate. This study used collecting technique of data for validity trying with data triangulation and theory triangulation. This study using data analyse with domain analyse model. Based on analysing of this study, Erlangga text book has fulfill requirements material accuration text book according to BSNP. Although, text book not to be perfect. In this book, finded a little bit mistakes. In this book, many knowledge finded about language and literature.